Clinicopathological profile, surgical management, and outcome of necrotising enterocolitis in children. - Jha Guarav; Kumar Pranay; Ashish Kumar (SJ Pediatrics and Child Health Africa, 2026)
Background Necrotizing enterocolitis (NEC) is a serious gastrointestinal emergency in neonates and infants, particularly among premature and low-birth-weight children. Early recognition and timely management are essential to reduce morbidity and mortality. This study evaluated the clinicopathological characteristics, management strategies, complications, and outcomes of children with NEC at a tertiary-care hospital. Methods A retrospective observational study was conducted at Patna Medical College and Hospital over a six-month period. Fourteen children diagnosed with NEC were included. Data regarding demographic characteristics, clinical presentation, management approach, complications, duration of hospitalisation, and survival outcomes were retrospectively reviewed. Patients were managed either conservatively or surgically according to clinical severity and disease progression. Results Among the 14 patients, 5 (35.7%) were managed conservatively, whereas 9 (64.3%) required surgical intervention. Complications occurred in 6 (42.9%) patients. The mean duration of hospitalisation was 14.2 ± 4.1 days. Overall, 10 (71.4%) patients survived, while 4 (28.6%) died. Delayed presentation was significantly associated with poor outcomes (p < 0.05). The findings indicate that patients requiring surgery represented a substantial proportion of the study population and experienced considerable morbidity. Conclusion NEC remains a serious neonatal surgical emergency associated with substantial morbidity and mortality. Early diagnosis, appropriate conservative management, timely surgical intervention, infection control, and adequate neonatal intensive care are essential for improving outcomes. Recommendation Early recognition and prompt referral of suspected NEC cases to specialised neonatal and paediatric surgical centres should be strengthened to facilitate timely intervention and improve survival.